Long Time Asymptotic Behavior of Solution of Implicit Difference Scheme for a Semi-Linear Parabolic Equation (Journal of Computational Mathematics, 2021)
In this paper, the solution of back-Euler implicit difference scheme for a semi-linear parabolic equation is proved to converge to the solution of difference scheme for the corresponding semi-linear elliptic equation as $t$ tends to infinity. The long asymptotic behavior of its discrete solution is obtained which is analogous to that of its continuous solution. At last, a few results are also presented for Crank-Nicolson scheme.